Plasma 11-Hydroxycorticosteroid and Growth Hormone Levels in Acute Medical Illnesses - Jacobs, H. S. (1969)
Adrenal cortical response in acute medical illness has been studied by measuring the plasma 11-hydroxycorticosteroid (11-OHCS) concentration in 178 patients. Those with unbalanced diabetes, acute infections, and severe myocardial infarction had high levels. The results obtained suggest that in a patient with a severe infection and hypotension a plasma 11-OHCS level of less than 15 μg./100 ml. indicates an inadequate adrenal cortical response, and one patient with septicaemia and temporary adrenal cortical insufficiency is described. Growth hormone levels were increased in patients with severe diabetic ketosis but not in those with hyperosmolar non-ketotic diabetic coma.